Ictal 99mTc-Ethyl Cysteinate Dimer SPECT Findings of a Girl With Refractory Localization-Related Epilepsy Who Developed Transient Ictal Bradycardia. Issue 3 (20th July 2015) - Kimizu, Tomokazu; Toshikawa, Hiromitsu; Kimura, Sadami; Ikeda, Tae; Mogami, Yukiko; Yanagihara, Keiko; Kishima, Haruhiko; Suzuki, Yasuhiro
Ictal bradycardia, which is considered to be one of the causes of sudden unexplained death in epilepsy, is rare. A 10-year-old girl with focal cortical dysplasia in her right centroparietal region developed transient ictal bradycardia during cluster seizures. Brain magnetic resonance imaging demonstrated a high signal intensity lesion adjacent to the focal cortical dysplasia lesion. Ictal 99m Tc-ethyl cysteinate dimer single-photon emission computed tomography (SPECT) detected hyperperfusion in an area containing the high signal intensity lesion, which was located close to the insular cortex. Since the hyperperfusion zone observed on SPECT was considered to reflect seizure propagation, it is possible that the ictal bradycardia experienced in the present case was caused by the following mechanism: The repetitive seizure activity caused the high-intensity lesion seen on MRI to expand into the right insular cortex, which controls cardiac rhythm, resulting in ictal bradycardia.